SAT0639 Biologic-eligible rheumatoid arthritis patients demonstrate absence of synovitis – utility of ultrasound in the management of ra-biologic population. (15th June 2017) - Naraghi, K; Vojinovic, T; Nam, J; Freeston, J; Emery, P; Wakefield, RJ; Buch, MH
Abstract : Background: Biologic drugs act by suppressing synovitis in patients with rheumatoid arthritis (RA). Clinical disease activity scores (DAS) are used to determine eligibility and assess biologic drug response. However, several drivers aside from synovitis may drive the DAS. Joint ultrasound (US) scan is more accurate than clinical examination in detecting inflammatory synovitis [1, 2], and is frequently used in clinical practice to assess need for biologic drug change [3]. Objectives: To phenotype DAS using US in patients eligible for a first/switch in biologic therapy and to evaluate whether and how this changed decision making. Methods: A retrospective evaluation of RA patients who attended our tertiary centre biologic clinic between 2014 and 2016 and had an US to clarify basis for raised disease activity. Three-variable DAS28-CRP 28 joints (DAS28-CRP) was recorded and US reports were evaluated to determine which of the following characteristics were observed: presence of synovitis, tenosynovitis, osteoarthritis, tendinopathy and no abnormality. Clinic notes were reviewed to record change in the management of patients as a result of combined clinical and US scan findings. Results: We identified 70 patients who had not received steroids within 4 weeks of the US, 84.3% female, median (range) age 58 (20–88) years. 66 (94.3%) patients were biologic experienced with 59 on ongoing treatment [3 (5.1%) abatacept, 22 (37.3%) anti-TNFα, 22 (37.3%) rituximab and 12 (20.3%) tocilizumab] of whom 47 (79.7%) were on combination with csDMARD therapy. 4 (5.7%) patients were biologic naive. 42 (63.6%) of bio-experienced patients, had a DAS28 ≥3.2 and were eligible for a change in their biologic however, only 17 of these patients had US-confirmed synovitis, 21 had evidence of osteoarthritis (OA), 1 tenosynovitis and 3 had no abnormalities. All biologic naïve patients had DAS28-CRP ≤5.1 before US however, 3 had US-confirmed synovitis and 1 had OA. Of bio-experienced, 13/66 (19.4%) patients, including 4 with DAS-28 <3.2 but US-confirmed synovitis, had a new biologic started. 3 rituximab patients (including one with subclinical synovitis) had re-treatment. Concomitant treatment was escalated in 13 (24.2%) patients. 35 (53.0%) patients, including 4 with US synovitis/tenosynovitis, had no change in their treatment. 2 (3.0%) patients self-discontinued treatment. Conclusions: By identifying lack of inflammatory synovitis in biologic eligible patients US reduced the need for unnecessary and costly change of biologics. US also detected subclinical synovitis warranting modification of their treatment. References: Colebatch AN, Edwards CJ, Ostergaard M, et al. EULAR recommendations for the use of imaging of the joints in the clinical management of rheumatoid arthritis. Annals of the rheumatic diseases. 2013; 72:804–814. Saleem B, Brown AK, Keen H, et al. Should imaging be a component of rheumatoid arthritis remission criteria? A comparison between traditional and modified composite remission scores and imaging assessments. Annals of the rheumatic diseases. 2011; 70:792–798. Iagnocco A, Finucci A, Ceccarelli F, et al. Power Doppler ultrasound monitoring of response to anti-tumour necrosis factor alpha treatment in patients with rheumatoid arthritis. Rheumatology (Oxford). 2015; 54:1890–1896. Disclosure of Interest: None declared